Impact of Enzymatic Hydrolysis on Antioxidant Activity of Snakehead Fish (Channa striata) Head Protein Hydrolysate - Venny Agustin; Masagus Muhammad Prima Putra; Amir Husni (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Snakehead fish head possess high protein content and potential to be used as materials for protein hydrolysate Snakehead fish head protein hydrolysis optimum condition were determined Snakehead fish head hydrolysate protein antioxidant activity were analyzed Snakehead fish head is potential to be used as materials for fish protein hydrolysate Abstract There is concern regarding the use of synthetic antioxidants which spurred the yearly increase of natural antioxidants to substitute synthetic ones. Fish protein hydrolysate (FPH), which has been reported to have potent antioxidant properties, could be utilized to solve this problem. This study aimed to utilize the by-product of snakehead fish (head) and determine the optimum hydrolysis conditions to obtain FPH with antioxidant activity. Two parameters were tested during the hydrolysis process: enzyme concentration (papain enzyme) and hydrolysis time. The optimum condition was evaluated by measuring dissolved protein, hydrolysis degree (DH), and antioxidant activity, including DPPH, ABTS, and FRAP. The optimal hydrolysis conditions were 5% enzyme concentration and 6 h of hydrolysis time at 55°C and pH 7.0. The DPPH, ABTS, and FRAP antioxidant activities were 50.70%, 66.67%, and 1.35 M Tr/mg, respectively. Based on the antioxidant activity, Snakehead fish head has the potential as a source of natural antioxidants.